The Influence of Ouabain on Human Dendritic Cells Maturation - C. R. Nascimento; R. C. Valente; J. Echevarria-Lima; C. F. L. Fontes; L. de Araujo-Martins; E. G. Araujo; V. M. Rumjanek (Mediators of Inflammation)
Although known as a Na,K-ATPase inhibitor, several other cellular and systemic actions have been ascribed to the steroid Ouabain (Oua). Particularly in the immune system, our group showed that Ouabain acts on decreasing lymphocyte proliferation, synergizing with glucocorticoids in spontaneous thymocyte apoptosis, and also lessening CD14 expression and blocking CD16 upregulation on human monocytes. However, Ouabain effects on dendritic cells (DCs) were not explored so far. Considering the peculiar plasticity and the importance of DCs in immune responses, the aim of our study was to investigate DC maturation under Ouabain influence. To generate immature DCs, human monocytes were cultured with IL-4 and GM-CSF (5 days). To investigate Ouabain role on DC activation, DCs were stimulated with TNF-α for 48 h in the presence or absence of Ouabain. TNF-induced CD83 expression and IL-12 production were abolished in DCs incubated with 100 nM Ouabain, though DC functional capacity concerning lymphocyte activation remained unaltered. Nevertheless, TNF-α-induced antigen capture downregulation, another maturation marker, occurred even in the presence of Ouabain. Besides, Ouabain increased HLA-DR and CD86 expression, whereas CD80 expression was maintained. Collectively, our results suggest that DCs respond to Ouabain maturating into a distinct category, possibly contributing to the balance between immunity and tolerance.